2019
DOI: 10.1002/jcb.28957
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of IGF‐IIRα intensifies doxorubicin‐induced cardiac damage

Abstract: Cardiotoxicity by doxorubicin hampers its therapeutic potential as an anticancer drug, but mechanisms leading to cardiotoxicity remain contentious. Through this study, the functional contribution of insulin‐like growth factor receptor type II α (IGF‐IIRα) which is a novel stress‐inducible protein was explored in doxorubicin‐induced cardiac stress. Employing both in vitro H9c2 cells and in vivo transgenic rat models (SD‐TG [IGF‐IIRα]) overexpressing IGF‐IIRα specifically in heart, we found that IGF‐IIRα leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Through this study, we examined the impact of β-catenin in Ang-II induced hypertrophy responses and demonstrated that IGF-IIR expression could be regulated by β-catenin/LEF1 leading to pathological cardiac hypertrophy signaling. Our earlier studies have shown that abnormal activation of IGF-IIR signaling pathway during cardiac stresses such as elevated Ang II levels [3], or high glucose [5], or drug-induced (doxorubicin) cardiotoxicity [12,13] could lead to increased hypertrophy, fibrosis, and cardiac apoptosis paving the way for heart failure. Besides, we showed that enhancement of β-catenin in cardiomyocytes promotes apoptosis and fibrosis during cardiac stresses such as myocardial infarction (MI) or diabetes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Through this study, we examined the impact of β-catenin in Ang-II induced hypertrophy responses and demonstrated that IGF-IIR expression could be regulated by β-catenin/LEF1 leading to pathological cardiac hypertrophy signaling. Our earlier studies have shown that abnormal activation of IGF-IIR signaling pathway during cardiac stresses such as elevated Ang II levels [3], or high glucose [5], or drug-induced (doxorubicin) cardiotoxicity [12,13] could lead to increased hypertrophy, fibrosis, and cardiac apoptosis paving the way for heart failure. Besides, we showed that enhancement of β-catenin in cardiomyocytes promotes apoptosis and fibrosis during cardiac stresses such as myocardial infarction (MI) or diabetes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo models have shown that MAPK signaling hypertrophy and mitochondrial-dependent apoptosis are activated; however, the PI3K-AKT survival cascade is attenuated when IGF-IIRα is specifically expressed in cardiomyocytes and cardiac tissues. 43 IGF-IIRα overexpression in the heart not only causes pathological heart, but also leads to hypertrophic kidney, 44 liver, and testis (unpublished data) in the transgenic rats. In the diabetic transgenic rats, collagen accumulation, renal tubular damage, and renal fibrosis are present in the pathological kidney by enhancement of STAT3 associated mechanism.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, doxorubicin‐induced functional and structural anomalies in the heart can be enhanced by IGF‐IIRα expression. Both in vitro and in vivo models have shown that MAPK signaling hypertrophy and mitochondrial‐dependent apoptosis are activated; however, the PI3K‐AKT survival cascade is attenuated when IGF‐IIRα is specifically expressed in cardiomyocytes and cardiac tissues 43 . IGF‐IIRα overexpression in the heart not only causes pathological heart, but also leads to hypertrophic kidney, 44 liver, and testis (unpublished data) in the transgenic rats.…”
Section: Discussionmentioning
confidence: 92%
“…Our previous studies show that IGFIIR is expressed during late stage cardiac events and an alternative splicing variant of IGFIIR named IGF-IIRα has been identified in pathological heart [ 11 , 12 ]. Elevated expression of IGF-IIRα during pathological conditions like diabetes and high salt worsens the cardiac performance and increases tissue damages [ 13 15 ]. A transgenic IGFIIRα overexpression rat model was created with cardiac specific Myh6 promoter.…”
Section: Introductionmentioning
confidence: 99%